Identification of Nias fingerprint patterns - Wau, Arminianti; Elviana, Ratu; Syamsurizal, S. (Tropical Genetics, 2024)
Fingerprints are one of the biological characteristics that can be used to confirm the identification of ethnic fingerprint patterns. Fingerprint patterns are a biological variation that differs from one racial group to another, between women and men and even identical twins. One of the races/tribes in Indonesia is the Nias tribe. This research is descriptive research with qualitative methods. Descriptive research is research that aims to describe, describe a phenomenon according to conditions in the field. The sample for this research is all Nias students at SMA Negeri 1 Pinangsori in the 2023/2024 academic year. The results of research on identifying fingerprint patterns of the Nias tribe at Pinangsori can be concluded that the most common fingerprint patterns are loop-shaped fingerprint patterns, namely 93%, whorl-shaped 7% and arch-shaped 0%. Apart from that, based on gender and age grouping, namely boys (14-19 years) and girls (14-18 years), the most common fingerprint pattern, namely the loop fingerprint pattern, is owned by 59% of female students and 59% of female students. male education is 34%. The whorl fingerprint pattern is mostly owned by male students, namely 4% and 3% of female students, while the arch fingerprint pattern is not shared by the entire sample group of Nias ethnic at Pinangsori.